Penggunaan Somatik Cell Count (SCC), Jumlah Bakteri dan California Mastitis Test (CMT) untuk Deteksi Mastitis pada Kambing - Adriani, Adriani (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
This study aimed to determine the use of the number of somatic cell  and of bacteria in milk and California Mastitis Test for the detection of mastitis in PE goat. 425 samples of milk from PE goats are kept  in  individual  cages and milked twice daily study used  in this study.   Before milking, goat udder was cleaned and greased with antiseptic (alcohol 70%) to kill bacteria that living on the teats and goat udders. SCC was observed  in the  stable, while milking. the number  of somatic cells and of bacteria of milk  samples of 150 ml took  into the cool-flask, and  laboratory analysis was done. The results  showed that there releathionship between somatic cell count, the number of bacteria and california mastitis milk tets  in  the detection of mastitis  in PE goats. The average SCC of PE goats was 288.1 x 103 cells  / ml with a range between 28.0 x 103 cells to  1991.7 x 103 cells / ml. The average number of bacteria in the milk of this study wss 537.9 x 103 cells / ml with a range between 66.5 x 103 and 2201 x 103 cells / ml milk. The average number of bacteria in the milk of this study was 537.9 x 103 cells / ml with a range between 66.5 x 103 and 2201 x 103 cells / ml milk. And the average score of CMT research was 2.34.  In conclusion, the use of somatic cell counts, bacterial counts and California mastitis test in goat milk can be used for the detection of mastitis in P E goats.